Improvement of productivity in a timber company through standardization and SMED tools with a lean approach - Verde Frech, Lawrence (2024)
This proposal aims to address the low productivity of a Peruvian timber SME through standardization and SMED tools, focusing on the Lean philosophy. The methodology unfolds in stages of diagnosis, improvement development with simulation and validation, and continuous improvement. It was identified that the processes and work methodologies at the cutting stations were inefficient and disorganized, resulting in significantly high time indicators negatively impacting production. As part of the development stage, SMED and standardization methodologies were applied, both generated through simulation in Arena 16.1 software. Following the simulation, the results demonstrated that the implementation of SMED and standardization would increase production by up to 28.84%, reduce downtime by 40%, and enhance resource utilization, thereby generating economic benefits for the company. This study aimed to advance the understanding of timber production and serve as a guide for other companies seeking to optimize processes and reduce costs through Lean Manufacturing principles. Its low-cost, high-impact approach could be replicable and beneficial to other companies in the sector.